Effect of humidity and temperature on drying of natural rubber - Varghese S; Cherian T; Kuriakose B (Natural Rubber Research, 2004)
The effect of temperature and relative humidity on drying of three froms natural rubber viz, rolled latex coagulum, latex coagulum crumb was studied by recording the percentage reduction in moisture content with time. Influence of the surface area on drying was demonstrated using yeast treated latex coagulum. Results indicated that larger portion of the drying time was for the second phase of drying(below 10;moisture), which involves diffusion of moisture from the coagulum. The rate of diffusion is influenced more by temperature of drying than by relative humidity.
Keywords: Diffusion; Diffusion; Drying; Drying; Moisture content; Moisture content; Natural rubber; Natural rubber; Relative humidity; Relative humidity; Sheet rubber; Sheet rubber